LEVEL SET-BASED TOPOLOGY OPTIMIZATION USING NONLINEAR PROGRAMMING: A PRELIMINARY STUDY (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Abstract. We investigate the numerical performance of a structural optimization method based on the level-set approach and using nonlinear programming. Besides the method of the moving asymptotes (MMA) and a globally convergent modification of it with a spectral correction,we have also considered sequential quadratic programming and interior-point methods as the nonlinear programming driving tools. We remark that the original formulation of the topology optimization problem may be addressed, without any need to penalize the constraints. Themethod was applied to the solution of some classical problems from the literature and the resultsobtained are encouraging. Keywords: Nonlinear programming, Level-set methods, Topology optimization, Structural optimization